Structure and Biology of Tissue Factor Pathway Inhibitor - Bajaj, Madhu S.; Birktoft, Jens J.; Steer, Sarah A.; Bajaj, S. Paul (Thrombosis and Haemostasis, 2001)
Human tissue factor pathway inhibitor (TFPI) is a modular protein comprised of three Kunitz type domains flanked by peptide segments that are less structured. The sequential order of the elements are: an N-terminal acidic region followed by the first Kunitz domain (K1), a linker region, a second Kunitz domain (K2), a second linker region, the third Kunitz domain (K3), and the C-terminal basic region. The K1 domain inhibits factor VIIa complexed to tissue factor (TF) while the K2 domain inhibits factor Xa. No direct protease inhibiting functions have been demonstrated for the K3 domain. Importantly, the Xa-TFPI complex is a much more potent inhibitor of the VIIa-TF than TFPI by itself. Furthermore, the C-terminal basic region of TFPI is required for rapid physiologic inhibition of coagulation and is needed for the inhibition of smooth muscle cell proliferation. Although a number of additional targets for attachment have been reported, the C-terminal basic region appears to play an important role in binding of TFPI to cell surfaces. A primary site of TFPI synthesis is endothelium and the endothelium-bound TFPI contributes to the antithrombotic potential of the vascular endothelium. Further, increased levels of plasma TFPI under septic conditions may represent endothelial dysfunction. We have proposed that the extravascular cells that synthesize TF also synthesize TFPI providing dual components necessary for the regulation of clotting in their microenvironment. Like the TF synthesis in these cells is augmented by serum, so is the case with the TFPI gene expression. TFPI gene knock out mice reveal embryonic lethality suggesting a possible role of this protein in early development. Since TF-induced coagulation is thought to play a significant role in many disease states, including disseminated intravascular clotting, sepsis, acute lung injury and cancer, recombinant TFPI may be a beneficial therapeutic agent in these disease states to attenuate pathologic clotting. The purpose of this review is to outline recent developments in the field related to the structural specificity and biology of TFPI.
Keywords: Factor VIIa; factor Xa; TFPI; tissue factor; Kunitz domains